PENGEMBANGAN STRATEGIS MUSEUM PERJUANGAN TNI SEBAGAI WISATA SEJARAH MEDAN: PENDEKATAN ANALISIS SWOT - Tambunan, Ellyta E. (Akademi Pariwisata Darma Agung, 2025)
This research aims to explore the strategic development potential of the Indonesian National Armed Forces (TNI) Struggle Museum in Medan as a historical tourism destination through comprehensive SWOT analysis. The study evaluates internal and external factors affecting museum development using External Factor Analysis Summary (EFAS) and Internal Factor Analysis Summary (IFAS) matrices. Using qualitative methodology, data were collected through observations, interviews with museum management and visitors, document analysis, and exhibition material review. The research involved 35 tourist respondents and museum management interviews. Results indicate the museum positioned in Quadrant I (Growth Strategy), with total IFAS score of 3.45 and EFAS score of 3.28, suggesting aggressive growth strategies should be implemented. Key strengths include unique military historical collections (502 artifacts), strategic location accessibility, and strong educational value. Main opportunities involve growing heritage tourism market and government support for cultural preservation. The study recommends implementing penetration strategies, facility enhancement, digital integration, and collaborative partnerships to maximize the museum's potential as a premier historical tourism destination.